Réponses

  • Utilisateur Brainly
2012-10-09T18:19:28+02:00

Coucou,

 

1) A=(3X-5)(5X+7)-(3X-5)(4X-1)

  = (3x * 5x + 3x * 7 + -5 * 5x + -5 *7)  - (3x*4x + 3x* -1 + -5* 4x + -5* -1)

  = 15x² + 21x -25x - 35 - ( 12x² - 3x -20x +5)

   = 15x² +21x -25x -35 - 12x² +3x +20x -5

  = 3x² + 19x - 40

 

2) essaie de factoriser, tu prends le résultat trouver avant

 

3) tu remplaces x par 0 puis -8 puis -3 dans ta formule donnée

2012-10-09T18:53:25+02:00

2) factoriser 

A = (3x-5) ( 5x+7) - (3x-5) ( 4x-1 ) 

A = (3x-5) ( 5x+7-4x+1 )

A = (3x-5) ( x+8)